A new online magazine devoted to “cultural studies”, «Comparative Cultural Studies: European and Latin America Perspectives»? What for? - Campani, Giovanna; Lombardi, Alessandra (Comparative Cultural Studies: European and Latin American Perspectives, 2016)
–